Implementation of the Amaliyah Values ​​of Aswaja an-Nahdliyah Through the Recitation of Yasin Fadhilah at INISNU Temanggung - Khoirin Zahwan, M. Zana; Ritonga, Wahyudi (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2025)
Yāsin is the 36th chapter of the Qur’an, comprising 83 verses; it was revealed after Sūrat al-Jinn and is classified as a Makkan surah. Fadīlah denotes merit or virtue, typically associated with devotional acts. This study aims to describe the practice of reciting Yāsin Fadīlah, a rendition the researcher translated from Arabic into Indonesian. The research employs a descriptive qualitative methodology with a sociological approach, treating the phenomenon as an expression of social relations among individuals and groups. Data were collected through observation, interviews, and document analysis. The findings indicate that the Yāsin Fadīlah ritual differs from ordinary Yāsin recitation in that it is interspersed with dhikr, salawāt, and various supplications. The text of Yāsin Fadīlah used in the practice is attributed to Muḥammad alFaqīh al-Muqaddam. The ritual typically begins with a tawassul, followed by the recitation of Yāsin Fadīlah, and concludes with a communal meal. Reported benefits associated with the practice include receiving Allah’s forgiveness, experiencing daily wellbeing, and the fulfillment of personal prayers, among others.